How to make “Sumedang” tofu: An ethnomathematics context from West Java - Harry Dwi Putra; Sendi Ramdhani (Journal of Honai Math)
Mathematics is one of the subjects that involves abstract concepts, which often poses difficulties for students in understanding the material. One solution to address these challenges is to connect mathematical concepts to students' everyday lives. Sumedang Tofu is a traditional food that is already familiar to students. The abstract mathematical concepts can be understood contextually through the production of Sumedang Tofu. This study aims to explore the mathematical concepts involved in the production of Sumedang Tofu that can be utilized in contextual learning. The research method employed is qualitative descriptive with an ethnographic approach. The research instruments consist of observation sheets, interview guidelines, and documentation sheets. Data collection techniques include direct observation at the Sumedang Tofu production site, interviews with Sumedang Tofu craftsmen, and photographs of the tools used in the production process. The collected data were analyzed using triangulation. The results indicate that in the production of Sumedang Tofu, there are concepts of flat shapes, such as squares and rectangles, as well as three-dimensional shapes, including cubes, rectangular prisms, and open-top cylinders. Additionally, concepts of division, proportionality, and congruence are also present. Sumedang Tofu can serve as a medium for contextual learning in teaching these mathematical concepts.